Comportamento das variáveis hemodinâmicas, autonômicas e metabólicas em mulheres menopausadas transplantadas renais ativas e sedentárias - FERREIRA, Andressa Coelho (2020)
Introduction: Additional factors increase cardiovascular risks in women after menopause, such as cardiometabolic disorders, insulin resistance, and dysfunction of the autonomic nervous system. These risks are even more aggravated with the presence of end-stage renal disease and a sedentary lifestyle. Although there is evidence regarding the benefits of exercise in patients undergoing renal replacement therapy, few studies have been directed at menopausal patients who have already undergone kidney transplantation. Objective: This study aims to evaluate the behavior of hemodynamic, autonomic and metabolic variables in active and sedentary renal transplanted menopausal women. Methods: This is an analytical cross-sectional study. This research included the participation of 16 menopausal kidney transplant patients allocated in two groups: active (N = 08, who underwent a combined training protocol lasting 60 minutes, 3x a week, for eight weeks) or sedentary (N = 08). Clinical history of patients, physical activity level, absolute hematimetric indices, and biochemical tests were evaluated. Subsequently, anthropometric assessment and body composition were measured, as well as the heart rate variability. Results: The sedentary and active groups had an average age of 44.60 and 48.00 years, respectively. Regarding the clinical characteristics of the patients, both groups presented comorbidities such as hypertension, diabetes mellitus and systemic lupus erythematous. Also, lower systolic blood pressure and higher glomerular filtration rate were observed in the active group, both presented moderate effect size. Regarding the analysis of body composition, the active group had a lower percentage of fat mass (28.85 ± 6.30 vs. 36.28 ± 5.22) and a higher percentage of lean mass (71.32 ± 6.30 vs. 63.72 ± 5.22). Concomitantly, this group had lower values of glucose (90.33 ± 7.79 mg/dL vs. 101.40 ± 2.19) and triglycerides (105.67 ± 3.06 mg/dL vs. 178.60 ± 57.67). As for analyzes of heart rate variability, differences between groups were observed with an increase in the root mean square of successive heartbeat interval differences (RMSSD) (21.50 ± 3.64 vs. 16.17 ± 2.47 ms), also in standard deviation-1 of the instant beat to-beat variability (SD1) (13,45 ± 1,21 vs. 9,15 ± 3,10 ms), and high frequency % (HF%) (48.00 ± 12.00 vs. 31.00 ± 7.00). Also, it was noted difference in the representative index of the sympathetic nervous system with lower value of low frequency in ms2 (LF ms 2 ) (86.83 ± 50.43 vs. 253.43 ± 172.41 ms2 ), low frequency % (LF%) (69.00 ± 7.00 vs. 52.00 ± 12.00), and sympathovagal balance (LF/HF) (1.19 ± 0.60 vs. 2.03 ± 0.80) in the active group. Conclusion: Menopausal women who have undergone kidney transplants and practice regular combined training have better variability of the cardiac autonomic nervous system, better control of glucose and triglyceride levels, and a lower percentage of fat, it was also noted a greater volume of lean mass compared to sedentary ones. Keywords: